The Influence of PBL Model with SDGs Approach on Students' Critical Thinking in Environmental Changes - Angela Diana Marthasari; Erna Heryanti; Daniar Setyo Rini (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
21st-century education demands 4C skills (communication, collaboration, creativity, and critical thinking) to support students’ understanding and knowledge. Essential thinking skills that are classified as low can be influenced by learning models. The Problem-Based Learning-Sustainable Development Goals model can be applied to train critical thinking skills. This research aims to determine the influence of the PBL-SDGs on essential thinking skills in environmental change issues. The research method uses a pretest-posttest control Group Design. The sample consisted of 66 students at 44 Jakarta Senior High Schools, with 33 students in each class selected using Simple Random Sampling. The essay instrument measures critical thinking skills based on the Ennis indicators. The data analysis method used descriptive analysis (minimum score, maximum score, mean, and standard deviation) and inferential (normality test, homogeneity test, and hypothesis test) statistical analysis. The research results show that the PBL-SDGs model can improve critical thinking skills, as seen from the N-gain in the experimental class of 0.607 and the control class of 0.505 in the medium category. The highest aspect of critical thinking skills in the experimental and control classes is Basic Support, with scores of 60,00 and 56,94. Based on the independent t-test, a significance of 0.005 < 0.05 is obtained, meaning the PBL-SDGs model influences critical thinking skills.